ETYMOLOGY OF LEXICAL UNITS EXPRESSING DYSPHEMISMS - Xo`jamova Yulduz,Ikramova Ra`no (International Journal of Literature and Language Studies, 2026)
This article investigates the etymological origins and semantic evolution of selected lexical units that function as dysphemisms in English and Uzbek. While dysphemisms are extensively studied in pragmatics for their role in face-threatening acts and social distancing, their historical linguistic development remains less explored. Through an examination of historical usage and semantic shifts, this study aims to identify common etymological pathways, such as semantic pejoration, metaphorical extension, and association with taboo or low-status concepts. The findings reveal that many dysphemisms originate from terms initially neutral or descriptive, acquiring their derogatory force through societal reinterpretation and metaphor. Understanding these etymological roots provides deeper insight into the cultural and historical underpinnings of linguistic aggression.